Penerapan hukum ekonomi riba sebagai antisipasi riba - Ilmi, Arizha Mahirotul (Maliki Interdisciplinary Journal, 2023)
Bank interest. bank interest, namely customers who offer the bank a number of benefits for services provided with funds deposited in the bank. However, bank interest can be considered illegal if the interest exceeds the limit or does not meet the requirements. In the Al-Quran it is stated that bank interest is included in usury and the law of usury is unlawful. Meanwhile, some experts are of the opinion that bank interest is legitimate, because it is intended as compensation with conditions that are not too high and according to the agreement of the parties, without feeling disadvantaged. Therefore, these differences of opinion can be synchronized with the findings of this study which show that bank interest is permissible as long as it is in accordance with the basic principles of sharia economic law which are applied to prevent usury.